Measuring resilience and fatality rate during the first wave of COVID-19 pandemic in Northern Italy: a note - Calogero Guccio (ZBW - Leibniz Information Centre for Economics, 2021)
During the first wave of the COVID-19 pandemic, much emphasis was placed on mortality indicators such as case-fatality rate and crude mortality rates to offer a preliminary assessment of the resilience between healthcare systems. The paper aims to contribute to the debate on the resilience of the healthcare systems during the pandemic by discussing whether the case-fatality rate and crude mortality indicators are appropriate for assessing resilience or whether other indicators should be employed. Comparing data obtained with different approaches based on statistical inference and large-scale serological survey, the article highlight, that great care must be taken when using case-fatality and crude mortality data, which in the absence of careful analysis, can lead to erroneous conclusions on the assessment of the resilience between healthcare systems. Furthermore, it shows that even in the absence of detailed epidemiological data new advancement in statistical methods can be useful to provide a more sounding evaluation of resilience.
Keywords: I10; I18; 330; Resilience; Missing data; Epidemiology; Novel coronavirus; Italy; Healthcare governance